PENGARUH METODE SMALL GROUP DISCUSSION TERHADAP HASIL BELAJAR IPA PESERTA DIDIK KELAS IV MIS DDI TAKKU KABUPATEN BARRU - Gusmini; Nurlina, A; Muafiah Nur (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to determine the effect of using the Small Group Discussion method on Science Learning Outcomes of Class IV Students, Mis DDI Takku, Barru Regency. This type of research is a quantitative research with a quasi-experimental form with nonequivalent control group design. The sample and population are class IV students of MIS DDI Takku, Tanete Riaja District, Barru Regency, totaling 29 students. The instruments used to collect data are pretest and posttest. The results showed that the data were analyzed using descriptive analysis and inferential analysis. Data were analyzed using descriptive statistical analysis techniques. It was found that the mean (mean) pretest in the Experiment Class was 29.79 while the mean (mean) Pretest in the Control Class was 28.47. The next descriptive analysis is that the average (mean) Posttest in the Experiment Class is 81.50 while the Posttest average (mean) in the Control Class is 68.00. The average value for the experimental class was higher than the control class after being given treatment. For inferential analysis using the t test formula, it is known that the tcount obtained from the experimental class is -13,454 and the tcount obtained from the control class is -10,617 with both classes having a frequency of df = 13, at a significant level = 0.05 or 5% obtained ttable is 2.160. So tcount > ttable or -13.454 > 2.160 this shows that H0 is rejected and H1 is accepted. Based on the results of this study, it can be concluded that there is an influence of the Small Group Discussion Method on Science Learning Outcomes of Class IV Students, Mis DDI Takku, Tanete Riaja District, Barru Regency.